“Pela salvação das crianças”: a experiência do Instituto de Proteção e Assistência à Infância do Ceará no combate à mortalidade infantil em Fortaleza (1913-1938) - Lima, Érica Cavalcante (2024)
This study aims to identify the speeches and actions that contributed to the creation of the Institute for Protection and Assistance to Children of Ceará – IPAI/CE, the first philanthropic institution providing health care for children in the state, as well as analyzing their experience in combating infant mortality in Fortaleza, in the period from 1913 to 1938 (includes the founding of the institute, implementation of the main actions carried out by it in combating infant mortality and the implementation of new public health policies of a governmental nature) which, in addition from purely clinical action with children, it took the form of a set of pedagogical practices towards mothers, particularly those from less favored classes, regarding “correct maternal exercise”. In view of this, this research seeks to analyze the ways in which the institution, under the legitimization of the fight against high rates of deaths among children, introduced, in practice, the precepts of Pediatrics and Childcare in the care of children's bodies, paving the way for for scientific medicine to enter the universe of motherhood, with the aim of transforming it according to medical regulations in the city of Fortaleza. To this end, a wide and varied range of documentary sources were used that contributed to the understanding of the context that involved the emergence of the creation of the Institute, as well as its activities with the city's population, among which, inspection reports of hygiene; reports, speeches, letters and messages from provincial presidents/governors; magazine and newspaper articles produced by intellectuals, engineers, graduates, doctors and politicians; medical theses; annals of scientific events, news from periodicals relating to the transition period between the 19th and 20th centuries, minutes of meetings and reports produced by the institution itself